Solution of Luzin's category problem on the existence of a primitive function - Ilmuradov, D. D. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
N. N. Luzin's problem on the existence of a primitive function is considered. We present a more precise formulation of the solution of this problem obtained by Landis.